The leaf anatomical trade-offs associated with plant ecological strategy variation - Simon Pierce; Dario Maffi; Franco Faoro; Bruno E. L. Cerabolini; Alberto Spada (Plant Ecology, 2022)
Plant functioning depends on variation in resource economics traits (acquisition vs. conservation) and the size of plants and their parts (the ‘global spectrum of plant form and function’). The anatomical basis of single traits (e.g., leaf mass per area; LMA) is generally understood, but little is known regarding the relationship between anatomical trade-offs and ecological strategies (representing integrated suites of traits). We hypothesised correlations between the relative extent of leaf tissue types and Grime’s Competitor Stress-tolerator Ruderal (CSR) strategies, principally a trade-off between structural (mechanical/fibro-vascular) vs. photosynthetic (chlorenchyma and intercellular airspace; ICAS) tissues, for ecologically contrasting herbaceous angiosperms in northern Italy. Specifically, that in the lamina portion, the trade-off represents the economics spectrum (S-R selection), but in the midvein portion, it reflects the mechanical constraints inherent to supporting large leaves (i.e., varies with C-selection). We used microscopy and image analysis to determine the relative cross-sectional area of tissues from transverse leaf sections (lamina and midvein portions) of angiosperms of contrasting CSR strategies. Principal components analysis (PCA) determined that the main trade-off (PCA1) was between mechanical/fibro-vascular tissues vs. ICAS/epidermis/chlorenchyma, but that this was associated with the economics spectrum (R- to S-selection) in the lamina, and with size (C-selection) for the midvein. A secondary trade-off in both lamina and midvein portions involved ICAS (i.e., the internal gas diffusion pathway) vs. chlorenchyma/epidermis (light capture), associated with S- to R-selection, respectively. Our results confirm the expectation that ecological strategy variation has a basis in underlying trade-offs between tissues with contrasting metabolic/architectural (i.e., economics/size-related) roles.